The College Scorecard, College Rankings, and Return on Investment - Dunlop, Michael (Archives of Business Research, 2018)
This paper explores the relationship between the College Scorecard, college ranking systems, and return on investment. Historically, there has been an emphasis, as well as popularity in ranking higher education institutions in terms of quality and job outcomes. This study utilized data from the United States Department of Education’s Federal College Scorecard and institutional ranking data from College Factual. A multiple regression analysis was used on the dependent variable of salary after attending, with the independent variables of college rank, graduation rate, and average annual cost. Best subsets regression modeling was used to determine the significance for each of the overall regression models, as well as the significance for each of the independent variables. The study included higher education institutions in the state of Massachusetts, USA. Analysis of the results offer several practical applications, interpretations, as well as recommendations for future research.